Komponen dan dampak lingkungan mikro dalam pengelolaan online marketplace - Sholihah, Nailatus (Maliki Interdisciplinary Journal, 2025)
The microenvironment is a factor that directly influences the operational activities and development strategies of an online marketplace. This study discusses the main components of the microenvironment, such as customers, sellers, competitors, service partners, and internal publics, and how each factor impacts the performance and sustainability of the platform. The results of the analysis show that changes in consumer behavior, seller quality, and the level of competition can determine the effectiveness of services and the competitiveness of marketplaces in the digital era. In addition, cooperation with supporting partners and the implementation of strong internal policies have been proven to increase user trust and loyalty. By comprehensively understanding the dynamics of the microenvironment, marketplace managers can formulate strategies that are more adaptive and responsive to market developments so as to maintain business sustainability.